Reliability Analysis of the Failure Data in Industrial Repairable Systems due to Equipment Risk Factors - M.A., Burhanuddin; Ghani, M.K. A.; Asmala, A.; Zuraida , Abal Abas; Zeratul Izzah, Mohd Yusoh (HIKARI Ltd, 2014)
Once a unit experiences a service downtime or downgrade; the covariates or risk factors can directly shows impact on the delay in repairing activities. In this paper, the risk factors are revealed that either delay or accelerate repair times, and it also demonstrates the extent of such delay, attributable to the underlying characteristics of the equipment. The potential risk factors provide necessary inputs in order to improve operation performance. Once risk factors are detected, the maintenance planners and maintenance supervisors are aware of the starting and finishing points for each repairing job due to their prior knowledge about the potential barriers and facilitators. This study employs semi-parametric approaches in a different way to examine the relationship between repair time and various risk factors of interest. The properties of the hazard function for the repair time problem are critically examined and the major findings are highlighted. This paper focused to estimate underlying characteristics of the machines during failures, which may prolong the troubleshooting time. An empirical study has been accomplished to estimate the risk factors. There are 1203 ir conditioners maintenance records in 2011 and 2012 are collected from food industries in Malaysia. The empirical studies estimates repair time data and background characteristics of the machines.